Influencing factors and adolescent input in custody arrangement decisions - Hartenstein, Jaimee L. (Kansas State University, 2014)
This study produces a grounded theory of how parents make decisions regarding the custody arrangements of their children in the divorce process. Eleven parent/adolescent pairs in shared physical and legal custody arrangements were interviewed. Ten factors were found to influence the custody arrangement decisions of divorcing parents: former partner, children, work, new partner, use of a lawyer, role of family, parenting role, place of residence, finances, and divorce. Parents also weighed perceived costs and rewards when making custody arrangement decisions. In addition, an understanding of the involvement of an adolescent in the custody arrangement decisions was gained through this research. The majority of adolescents in this study had some type of input in the custody arrangements at one point or another. Parents and adolescents both expressed concerns with involving adolescents in custody arrangement decisions as well as an appropriate age for adolescent involvement, and how to determine when an adolescent is ready to be involved in the custody arrangement decisions. Custody arrangement decisions are complex decisions that parents and adolescents face; a number of factors are considered and the custody arrangement decision making process varies for all families.
Keywords: Divorce; Custody arrangements; Adolescent input; Individual & Family Studies (0628); Social Research (0344)